A date in the cinema: Year 2000 (Journal of Parents and Teachers, 2014)
The year 2000 was perceived as the approach of a utopian frontier that progressively became a mere number on the calendar with its expected daily monotony.Nevertheless, cinema has always tried to take advantage of the mystery of a new millennium as, for example, in "2001: A Space Odyssey", a title that still admitted questions and possibilities based on the colossal deployment of space technology and the effective realisation of projects that previously occupied the place of the fantastic.
Keywords: millenium; cinema; films